Spark Plasma Sintering of a Gas Atomized Al7075 Alloy: Microstructure and Properties - Molnárová, Orsolya; Málek, Přemysl; Lukáč, František; Chráska, Tomáš (Materials (Basel, Switzerland), 2016)
The powder of an Al7075 alloy was prepared by gas atomization. A combination of cellular, columnar, and equiaxed dendritic-like morphology was observed in individual powder particles with continuous layers of intermetallic phases along boundaries. The cells are separated predominantly by high-angle boundaries, the areas with dendritic-like morphology usually have a similar crystallographic orientation. Spark plasma sintering resulted in a fully dense material with a microstructure similar to that of the powder material. The continuous layers of intermetallic phases are replaced by individual particles located along internal boundaries, coarse particles are formed at the surface of original powder particles. Microhardness measurements revealed both artificial and natural ageing behavior similar to that observed in ingot metallurgy material. The minimum microhardness of 81 HV, observed in the sample annealed at 300 °C, reflects the presence of coarse particles. The peak microhardness of 160 HV was observed in the sample annealed at 500 °C and then aged at room temperature. Compression tests confirmed high strength combined with sufficient plasticity. Annealing even at 500 °C does not significantly influence the distribution of grain sizes-about 45% of the area is occupied by grains with the size below 10 µm.
Keywords: gas atomized Al7075 alloy; microstructure; spark plasma sintering; high temperature stability; microhardness